Formulasi Inokulan Jamur Pembentuk Gubal Gaharu pada Tanaman Ketimunan (Gyrinops versteegii) - MEGA, I MADE; SUANDA, DEWA KETUT; KASNIARI, DESAK NYOMAN; SUENA, WAYAN; PARWATA, MADE ADI OKA (Agrotrop : Journal on Agriculture Science, 2014)
This study aims to find the most effective formulation of the gaharu agar wood forming fungi inoculants which infect Gyrinops versteegii plants, thus producing high quality agar wood. The method used in this research is the randomized block design (RBD) with three replication. The treatments were two fungi as inoculant applied saperately each and a combination of Rhisopus sp. and Fusarium sp. in the form of solid and liquid. The treatments tested were: (A) Fusarium solani fungi inoculant in solid form, (B) Rhisopus sp.fungi inoculant in solid form, (C) Mixture of Rhisopus sp. and Fusarium solani fungi inoculants in solid form, (D) Fusarium solani fungi inoculant in liquid form, (E) Rhisopus sp.fungi inoculants in liquid form, (F) Mixture of Rhisopus sp. and Fusarium solani fungi inoculants in liquid form, and (G) A combination of solid and liquid of Rhisopus sp. and Fusarium solani fungi inoculants. The parameters measured were the agar wood formed: agar wood fragrance level, color of agar wood and resin content of the agar wood. Furthermore, the data is analyzed statistically by analysis of variance. The results showed that, treatments of inoculants formulations significantly affects the aroma and resin content of agar wood. Formula of G (a combination of solid and liquid Rhisopus sp. and Fusarium solani fungi inoculants) and F (a combination of liquid Rhisopus sp. and Fusarium solani fungi inoculants) produced agar wood of the highest quality compared to other formulas. Formula G and F produced each agar wood with black and blackish-brown colour, with strong aroma (fragrance), and a resin content of 7.69% and 6.98%.
Keywords: agar wood, Rhisopus sp. and Fusarium inoculant, Gyrinops versteegii